2009
DOI: 10.37307/j.1868-775x.2009.02.09
|View full text |Cite
|
Sign up to set email alerts
|

Eine Sprach-Mauer in den Köpfen? Über aktuelle Spracheinstellungen in Ost und West

Abstract: Es gibt zwar schon seit dem Mauerfall einen populären Diskurs über die Verständigungsschwierigkeiten zwischen Ost-und Westdeutschen und über die sprachlichen Unterschiede auf beiden Seiten. Über die Meinungen und Einstellungen zu sprachlichen Fragen ist aber so gut wie nichts bekannt. In diesem Beitrag wird untersucht, wie (bzw. wie verschieden) die Deutschen in Ost und West über das Deutsche, über andere Sprachen, über Sprachgebrauch und Sprachpolitik denken. Dabei zeigt sich, dass statistisch gesehen die Gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This study is part of a larger project on early bilingualism involving SocL-German that examines HL-English as well, in a bid to investigate the potential of HL status differences on HL development. English is a high status language in German-speaking countries, whereas Polish is not (Plewnia and Rothe, 2011). The decision to focus on HL-Polish rather than other low status HL-languages in Germany such as HL-Russian or HL-Turkish (Plewnia and Rothe, 2011) was founded in the existence of several other studies on those HLs in Germany (see review above) and on the scarcity of studies there focusing on early HL-Polish development (see below).…”
Section: Substantive Contribution: a Focus On Hl-polish With German A...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project on early bilingualism involving SocL-German that examines HL-English as well, in a bid to investigate the potential of HL status differences on HL development. English is a high status language in German-speaking countries, whereas Polish is not (Plewnia and Rothe, 2011). The decision to focus on HL-Polish rather than other low status HL-languages in Germany such as HL-Russian or HL-Turkish (Plewnia and Rothe, 2011) was founded in the existence of several other studies on those HLs in Germany (see review above) and on the scarcity of studies there focusing on early HL-Polish development (see below).…”
Section: Substantive Contribution: a Focus On Hl-polish With German A...mentioning
confidence: 99%
“…English is a high status language in German-speaking countries, whereas Polish is not (Plewnia and Rothe, 2011). The decision to focus on HL-Polish rather than other low status HL-languages in Germany such as HL-Russian or HL-Turkish (Plewnia and Rothe, 2011) was founded in the existence of several other studies on those HLs in Germany (see review above) and on the scarcity of studies there focusing on early HL-Polish development (see below). Thus this study makes a substantive contribution as well, uncovering realities of language use and development within bilingual Polish-German preschoolers.…”
Section: Substantive Contribution: a Focus On Hl-polish With German A...mentioning
confidence: 99%
“…Work on language stereotypes, attitudes ( Johnson et al, 1999 ; Niedzielski, 1999 ; Hay and Drager, 2010 ; Jannedy and Weirich, 2014 ), and person perception ( Scherer, 1972 ; Schirmer, 2019 ) has shown that it is possible to put speakers in mind-sets in which to perceive speech. We will exploit this finding for our study, too by making listeners believe that a voice they hear either belongs to a French speaker learning German or a German speaker of Turkish decent, both groups for which stereotypes exist in dominant German language ideology ( Plewnia and Rothe, 2009 ; Jannedy and Weirich, 2014 ; Jannedy et al, 2019 ). While German spoken with a French accent supposedly is the most favored foreign accent by Germans and generally evokes positive ratings ( Plewnia and Rothe, 2009 ), German spoken with features believed to be of multi-ethnic origin, i.e., Arabic or Turkish seems to polarize or evoke negative stereotypes ( Wiese, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We will exploit this finding for our study, too by making listeners believe that a voice they hear either belongs to a French speaker learning German or a German speaker of Turkish decent, both groups for which stereotypes exist in dominant German language ideology ( Plewnia and Rothe, 2009 ; Jannedy and Weirich, 2014 ; Jannedy et al, 2019 ). While German spoken with a French accent supposedly is the most favored foreign accent by Germans and generally evokes positive ratings ( Plewnia and Rothe, 2009 ), German spoken with features believed to be of multi-ethnic origin, i.e., Arabic or Turkish seems to polarize or evoke negative stereotypes ( Wiese, 2015 ). It is our assumption that neither the positive nor the negative associations with these two varieties of German are conscious so as to be deliberately mediated in public, and moreover, vary between individuals influenced by social factors such as age or personal background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation